Ideologi dan Kesepadanan Penerjemahan Kata Bermuatan Budaya pada Buklet Pariwisata Situs “Wonderfull Indonesia: Yogyakarta” - Amalia, Annisa Jati Nur; Herniti, Ening (Deskripsi Bahasa, 2025)
This study aims to identify the ideology underlying the translation of culturally charged words in tourism booklets published by the Wonderful Indonesia website. This study aims to analyze the translation ideology and the equivalence of culturally loaded words found in the tourism brochure of the Wonderful Indonesia official website, specifically the Yogyakarta edition. The objective is to examine how translation strategies—whether domesticating or foreignizing—impact the level of equivalence in conveying cultural meanings, and how these choices reflect the translator's underlying ideological stance in representing Indonesian culture to international audiences. This research employs a qualitative approach, utilizing text analysis as its method. Data were collected through a literature study and content analysis of tourism booklets available on the Wonderful Indonesia website. The analysis process involved identifying culturally charged words and the ideologies present in the translation, taking into account the cultural context and purpose of communication. The results show that the translation of culturally charged words in tourism booklets serves not only as a communication tool, but also as a means to build a positive image of Indonesia. The underlying ideology of the translation reflects efforts to attract international tourists by emphasising the uniqueness and richness of Indonesian culture. However, there are also challenges in maintaining the authenticity of cultural meanings when translated into foreign languages. It is hoped that this research will contribute to the understanding of the relationship between translation, culture, and ideology in the context of tourism. The findings are particularly relevant for stakeholders in the tourism industry, as they inform the design of effective promotional materials that are sensitive to local cultural values and preferences. Thus, this research is expected to serve as a reference for the development of more inclusive and representative tourism communication strategies.